Memperkuat Pertahanan Laut Indonesia: Belajar dari Strategi Pertempuran Laut Rusia-Jepang, 1904-1905 - Hidayat, Cecep (Jurnal Sejarah Citra Lekha, 2024)
The Russo-Japanese War (1904-1905) was a significant event in the early 20th century that saw the two nations clash on various battlefields, both on land and at sea. This article aims to analyze the naval combat strategies employed during the Russo-Japanese War, with the objective of providing relevant insights for the Indonesian Navy (TNI AL). The primary focus of this analysis is the effectiveness of strategies such as naval blockades, visionary leadership, and the optimization of fleets and logistics, factors that are highly relevant for strengthening Indonesia’s maritime defense as an archipelagic nation. This article is based on a historical research approach, utilizing a variety of sources, including archives, books, magazines, journal articles, and other documents that contain pertinent information on the topic. The analysis reveals that six naval battles took place during the Russo-Japanese War, with Japan emerging victorious in five of them. In these battles, Japan implemented an aggressive naval blockade strategy, supported by effective leadership, a superior fleet and armament, as well as a well-organized logistics system. Based on these findings, the researcher recommends that the TNI AL develop a naval combat operation plan tailored to Indonesia’s specific maritime conditions, in order to strengthen its deterrent capabilities and national maritime defense.